Hydrogeochemical Characterization and Subsurface Flow Analysis of Volcanic Hot Springs - Riogilang, Hendra; Octovian Berty Alexander Sompie; Riogilang, Herawaty (Advance Sustainable Science Engineering and Technology, 2025)
Understanding of the hydrogeochemical system of volcanic hot springs in Tompaso, Minahasa, is still limited, especially regarding the origin of water and subsurface flow patterns. This study aims to classify geothermal water types and analyze groundwater flow systems in volcanic environments. A total of 15 hot spring samples were analyzed using field measurements (temperature, pH, electrical conductivity), ion chromatography, titration, and spectrophotometry. Data validation was done with ion balance, and water classification using Piper diagrams. The results showed four main types of water, namely Mg-SO₄, H-SO₄, Na-Cl, and Na-SO₄. Most of the samples are from meteoric water directly heated by the geothermal system, while two samples (HT-11A and HT-11B) were heated by steam. These findings provide a scientific basis for sustainable geothermal exploration and groundwater conservation in volcanic areas with variable geothermal systems at the study site